The Assessment Center Strategy in Educator Selection to Improve the Quality of Education in New Schools - Wahyuningsih, Sri Wulan; Khikmah, Siti Futukhatul; Harliawan; Muazza; Aprillitzavivayarti (Al-Qalam Institue, 2025)
This study analyzes the use of the Assessment Center strategy to select educators and strengthen the quality of human resources in new schools. The recruitment of qualified teaching staff is crucial, yet conventional selection methods, such as administrative reviews and general interviews, often fail to assess the holistic competencies required of professional educators. This literature-based study synthesizes findings from scientific journals, books, and academic reports to examine the effectiveness of Assessment Center components, including competency-based interviews, teaching simulations, and group discussions. Using a descriptive analysis approach, the study evaluates how these components assess cognitive, pedagogical, social, and personality competencies in an integrated manner. The findings show that Assessment Centers provide a more objective, valid, and comprehensive evaluation compared to traditional methods. They enable schools to identify prospective educators whose skills, values, and behavioral characteristics align with institutional needs and cultural expectations. This strategy enhances the accuracy of recruitment decisions and supports the development of a professional, collaborative, and reflective teaching workforce. The study concludes that Assessment Centers are an effective tool for improving the quality of educator selection and can serve as a strategic foundation for building quality-oriented education in new schools.